Adaptive collaborative management: criteria and indicators for assessing sustainability - Pokorny, B.; Cayres, G.; Nunes, W.; Segebart, D.; Drude, R.; Steinbrenner, M. (Center for International Forestry Research, 2003)
Adaptive Collaborative Management (ACM) is an integrative approach for implementing sustainable management of natural resources, based on a main hypothesis, that is: if there is a high degree of collaboration between stakeholders combined with a high adaptiveness of management systems, the result will be a higher degree of human well being and ecological sustainability. A worldwide network under the umbrella of the Center for International Forestry Research (CIFOR) is engaged in researching the potential and methodological aspects related to ACM. Communication is fundamental for facilitating the collaboration between the stakeholders. To support this communication and to enable a transparent and efficient discussion about sustainable forest management by rural communities, we developed an ACM set of criteria and indicators (C&I), which is presented here.